2022
DOI: 10.1021/acsenergylett.2c02742
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions of A-Site Cations Modulate Stability of 2D Metal Halide Perovskites

Abstract: Controlling the chemical properties of A-site cations in 2D metal halide perovskites (MHPs) and in 2D/3D assemblies is key to stable and efficient optoelectronic devices. Here, we rationalize the chemical interactions of different classes of organic cations in 2D MHPs, which are responsible for material stability in 2D and 2D/3D heterojunctions. Our results emphasize potential enhancement in stability by hydrogen bonding within the organic framework, showing substantially stronger intermolecular interaction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Furthermore, the intermolecular interaction of the passivating agent makes the difference to the whole binding energy, hence leading to stabilizing behavior of the adsorbed molecules on the HOIP surface. This feature has been partially addressed in layered quasi-2D perovskites 58,59 and is also evidenced by a similar charge density difference profile produced on the molecule–surface bonding region, as seen in Fig. S1 †.…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, the intermolecular interaction of the passivating agent makes the difference to the whole binding energy, hence leading to stabilizing behavior of the adsorbed molecules on the HOIP surface. This feature has been partially addressed in layered quasi-2D perovskites 58,59 and is also evidenced by a similar charge density difference profile produced on the molecule–surface bonding region, as seen in Fig. S1 †.…”
Section: Resultssupporting
confidence: 54%
“…The stronger hydrogen bonding enhances the internal stability and improves the electronic properties of halide perovskites. 63,69,70 Overall, along with molecular interlayer packing, the dynamic coupling between inorganic and organic moieties also gets modified with the functionalization of the spacer cations. Several studies have reported the complex impact of spacers on the dynamic structure and optoelectronic properties, including charge carrier transport in layered halide perovskites.…”
Section: Static Structural Propertiesmentioning
confidence: 99%
“…From a theoretical perspective, vertical charge transport in 2D perovskites is still a relatively unexplored area. Several computational works have screened potential 2D perovskite candidates by estimating the carrier effective mass along the out-of-plane direction. , Other groups have investigated the chemical interactions between spacer cations and the inorganic layer in 2D perovskites using first-principles calculations. The Rothlisberger group proposed a simple barrier model to quantify the interlayer tunneling probability of 2D perovskites . The insulating nature of the spacer cation is reflected by the rather small tunneling probability in the out-of-plane direction.…”
Section: Introductionmentioning
confidence: 99%